PENGAMPUNAN HAKIM (JUDICIAL PARDON): SEBUAH KONSEPTUAL MENUJU KEADILAN SUBSTANSIAL - Reski Anwar (Fakultas Syariah dan Ekonomi Islam, 2023)
Abstract: The context of judicial pardon will be the focus of this journal. As a form of substansial justice, the current national Criminal Code recognizes the principle of pardoning judicials, especially for minor offenses involving short-term deprivation of rights. Additionally, this tenet can act as a foundation for balancing justice in society. Through the regulation of judge pardons in the national Criminal Code, efforts to reform material criminal laws are serious issues that require special attention. The way a judge grants a pardon is written suggests that the government wants to go back to how it was before in order to do justice and do it well. In order to account for a judicial's pardon, special conditions or restrictions are used as a reference point. It is impossible to combine the position of a judicial's pardon and its application in a decision, specifically a judicial's pardon decision, into a single free or adjudicated decision; rather, each decision must be considered separately. The draft Criminal Procedure Code and the current Criminal Procedure Code, which will soon be able to accommodate and serve as a direct bridge to prevent this article on the judge's pardon from becoming a wasted article also known as a death sentence are both in this position. Keywords: Judicial Pardon, Rechterlijk Pardon, Substantial Justice Abstrak: Jurnal ini secara khusus akan membahas pengaturan pemaafan hakim (judicial pardon). Pada KUHP nasional saat ini sudah mengenal yang namanya asas pemaafan hakim sebagai bentuk keadilan substansial yang bertujuan untuk sedapat mungkin menghindari hukuman penjara, terutama untuk kejahatan ringan yang melibatkan perampasan hak dalam jangka pendek. Asas ini juga bisa sebagai fondasi sebagai pedoman untuk menyeimbangkan keadilan yang ada didalam masyarakat. Upaya pembenahan undang-undang pidana materiil melalui pengaturan pengampunan hakim dalam KUHP nasional merupakan persoalan serius yang perlu menjadi perhatian khusus. Rumusan mengenai pengampunan hakim mengandung makna bahwa pemerintah berkeinginan untuk kembali kepada keadaan semula demi mewujudkan keadilan dan kembali kepada keadilan yang substansial. Batasan atau syarat khusus dijadikan tolak ukur dalam perumusan pengampunan hakim agar dapat dipertanggungjawabkan. Kedudukan pengampunan hakim dan penerapannya dalam suatu putusan, yaitu putusan pengampunan hakim, tidak dapat dirumuskan menjadi satu putusan, baik bebas maupun putusan, melainkan menjadi putusan tersendiri. KUHAP saat ini dan Rancangan KUHAP yang akan datang secepatnya bisamengakomodir dan menjembatani langsung agar pasal pengampunan hakim ini tidak menjadi pasal yang terbuang sia-sia alias pasal mati. Kata Kunci: Pengampunan, Pemaafan Hakim, Keadilan Substansial